Rosai and Dorfman Disease with Pleural Involvement: Case Report - Jouda Cherif; Sonia Toujani; Nadia Mehiri; Bechir Louzir; Nidham Kchir; Majed Beji (The Scientific World Journal)
Sinus histiocytosis with massive lymphadenopathy (SHLM) disease is considered to be an indolent and self-limiting pathology. However, severe morbidity and mortality have been attributed to complications of SHLM. Lower respiratory tract involvement is rarely reported and is often unfavorable, and carries a particularly grave prognosis. A case of SHLM is reported, in which the patient had lower respiratory and pleural involvement.